Pengaruh Indikator Kualitas Pelayanan Terhadap Kepuasan Pelanggan: Studi di Alfamart Jalan Diponegoro Bojonegoro - Noor, Fauzian; Anggapratama, Reza (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Alfamart Jalan Diponegoro Bojonegoro is a retail business developing rapidly, selling daily necessities and offering convenience because its location is easy to reach and close to buyers. This organization is on Jalan Diponegoro, Bojonegoro Regency, East Java Region. Organizations today face increasingly fierce competition to increase consumer loyalty. So it is necessary to investigate which plans can determine the factors that influence service quality on consumer loyalty, determine the characteristics that fundamentally influence consumer loyalty and determine the degree of service quality provided by Alfamart Jalan Diponegoro Bojonegoro on consumer loyalty. Quantitative research is used in this type of research. The examination strategy uses fascinating investigations. The f-test results obtained a very large value of 0.000. This means there is a very large influence between physical evidence, reliability, responsiveness, guarantee and empathy on customer satisfaction, with an impact level of 58.4% and more than 41.60% influenced by various factors not included in this research.